Mechanical properties and damage model of coral seawater sea sand concrete under compression-shear composite action - Jintuan Zhang; Fenglun Jia; Yuliang Chen; Peihuan Ye (Case Studies in Construction Materials, 2023)
The present study investigates the mechanical properties of coral seawater sea sand concrete (CSSC) under compression-shear composite action. A total of 54 concrete specimens were designed for the shear test with varying parameters such as normal stress ratio, curing age and different aggregate types considered. The CSSC shear stress-displacement curve was obtained by observing the damage morphology of the specimen under a combination of compressive and shear stresses. The effects of different normal stress ratios on the shear strength, peak shear displacement, and damage evolution pattern of the CSSC specimen are analyzed. The results show that the width of the main cracks on the surface of the specimen gradually increases with the normal stress ratio, and the tiny oblique cracks gradually become denser. The peak shear displacement and shear strength also increase with normal stress, and the damage evolution of the concrete gradually slows down. When the curing age was increased from 7d to 14d and 28d, the shear strength of the CSSC specimens increased by 5.9% and 11.3%, respectively. In this paper, we propose two failure models that better reflect the shear strength of CSSC under the combined action of compression and shear. Finally, a compressive-shear damage constitutive model for CSSC at different normal stress ratios has been developed and the results are in good agreement with the experimental results.